Structural Funds and Economic Divide in Italy - Aiello Francesco; Pupo Valeria (European Regional Science Association (ERSA), 2010)
This paper provides a contribution to the debate on the role of EU cohesion policy in Italy. The focus is on the territorial effects of EU spending from 1996 to 2007. The empirical analysis considers a neoclassical growth model which is augmented by the structural funds spent by each region. Using panel data and a dynamic panel estimator we find that the structural funds, even having had a greater impact in the South compared to the Centre-North, have not contributed to reduce the economic divide in Italy.
Keywords: H50; R58; O47; 330; Structural Funds; Regional Policy; Economic Divide in Italy